USE OF (POMACEA CANALICULANTA) SHELL FOR THE REMOVAL OF LEAD FORM AQUEOUS SOLUTIONS - Sama A. Mustafa,; Ali K. Al-Muttairi,; Zahraa Hussein Obaid,; Shaimaa Satae M. Ali, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This study was aimed to find a new, cheap available adsorbent for the removing of Pb from water, using shells of Mollusca (Pomacea canaliculanta). In order to estimate the efficiency of the new adsorbent in removing the heavy metal, batch experiments were achived. At the beginning the best contact time was determined which is equal to 2 hours. then the effect of the initial lead concentrations was studied which demonstrated a direct correlation between the removal efficiency of the adsorbent and the Pb concentration up to 93.98 percent at lead concentration of 60 ppm. After that the effect of adsorbent weight on the removal of the metal was examined which show that 0.75 gm give the best removal efficiency up to 79.08 of the lead initial concentration, as well as the pH value effect on the lead adsorption was evaluated. The results show that the proposed adsorbent has a very good ability for removing the lead, through the whole experiments.